(untitled) (International Seven Journal of Multidisciplinary, 2025)
This article addresses the social inclusion and learning process of children with Autism Spectrum Disorder (ASD) in Early Childhood Education, aiming to understand how schools can foster the comprehensive development and active participation of these children in the school environment. The research is bibliographic in nature and was developed through the analysis of academic works, legal documents, and recent studies on inclusive education, autism, and pedagogical practices in early childhood. The investigation is based on the premise that the presence of a child with ASD in school does not, in itself, guarantee effective inclusion. It is necessary to rethink structures, relationships, and teaching methodologies to ensure acceptance and appreciation of their specificities. The study emphasizes the importance of a pedagogical approach sensitive to differences, based on careful observation and respect for each child’s individual pace. Furthermore, it highlights the importance of collaborative work between teachers, families, and multidisciplinary teams, as well as the fundamental role of continuing teacher training in addressing the challenges of inclusion. The results of the analysis indicate that planned pedagogical practices, combined with the ethical commitment of education professionals, can promote meaningful learning experiences, contributing to the development of communication, socialization, and autonomy in children with ASD. The conclusion is that social inclusion in early childhood education must be understood as an ongoing process of transformation, requiring collective engagement and effective public policies to fully guarantee the right to education. Building an inclusive school, therefore, not only benefits children with disabilities but also strengthens the principles of equity, coexistence, and respect for diversity for the entire school community.